Photobiomodulation of freshly isolated human adipose tissue‐derived stromal vascular fraction cells by pulsed light‐emitting diodes for direct clinical application. (1st May 2018) - Priglinger, E.; Maier, J.; Chaudary, S.; Lindner, C.; Wurzer, C.; Rieger, S.; Redl, H.; Wolbank, S.; Dungel, P.
Abstract: A highly interesting source for adult stem cells is adipose tissue, from which the stromal vascular fraction (SVF)—a heterogeneous cell population including the adipose‐derived stromal/stem cells—can be obtained. To enhance the regenerative potential of freshly isolated SVF cells, low‐level light therapy (LLLT) was used. The effects of pulsed blue (475 nm), green (516 nm), and red (635 nm) light from light‐emitting diodes applied on freshly isolated SVF were analysed regarding cell phenotype, cell number, viability, adenosine triphosphate content, cytotoxicity, and proliferation but also osteogenic, adipogenic, and proangiogenic differentiation potential. The colony‐forming unit fibroblast assay revealed a significantly increased colony size after LLLT with red light compared with untreated cells, whereas the frequency of colony‐forming cells was not affected. LLLT with green and red light resulted in a stronger capacity to form vascular tubes by SVF when cultured within 3D fibrin matrices compared with untreated cells, which was corroborated by increased number and length of the single tubes and a significantly higher concentration of vascular endothelial growth factor. Our study showed beneficial effects after LLLT on the vascularization potential and proliferation capacity of SVF cells. Therefore, LLLT using pulsed light‐emitting diode light might represent a new approach for activation of freshly isolated SVF cells for direct clinical application.